Strategi Promosi dalam Meningkatkan Brand Awareness Produk Bibir Wardah Cosmetics Melalui Konten Instagram Reels Campus Ambassador di Kalangan Mahasiswa - Annissa Latifa Salsabila; Muchamad Rizqi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The number of marketers who develop advertisements through content marketing is followed by the development of social media features, one of which is the use of content marketing with Instagram reels. This study uses a qualitative method using a design thinking approach. The design thinking approach is used to determine the promotion strategy of Wardah Cosmetics lip products through Instagram Reels content to increase brand awareness among students. The results of this study indicate the high account insight achieved through Instagram Reels content, Wardah Cosmetics can use campus ambassadors to further increase brand awareness among students even though Wardah has achieved top of mind in brand awareness.